The Role of a Buddhist Monk in Local Development: Science Communication from a Local Thai Context - Supakata, Nuta (Asian Health, Science and Technology Reports, 2011)
This study aims to identify and analyze the role and processes of mediators in bridging two knowledges by using the SECI Model of Ikujiro Nonaka as a tool to investigate knowledge creation directed by a mediator. Because of the difficulty of linking Thai local wisdom and science & technology, in this case Phra Somkid Jaranathummo, a Buddhist monk from Wat (temple) Pongkhum as mediator played a significant role in connecting these two areas of knowledge. To conserve and to systematically develop knowledge of natural dyed cotton woven textile as an alternative in order to nurture village self-reliance, Phra Somkid Jaranathummo, initiated a research named “The development processes of natural-dyed fabric production at Wat Pongkhum”, a participatory action research which had financial support from the Thailand Research Fund (TRF).